THU0511 Tocilizumab is a promising treatment option for therapy resistent juvenile localised scleroderma patients. (15th June 2017) - Foeldvari, I; Anton, J; Friswell, M; Bica, B; Inocencio, J de; Aquilani, A; Helmus, N
Abstract : Background: Juvenile localised scleroderma (jlSc) is an orphan disease. Most patient respond to treatment ot methotrexate or mycophenolate. In case of nonresponse or partial response, based on the promising tocilizumab (TOC) data of adult systemic sclerosis studies, TOC seems to be a promising option. There is no publication regarding the effectiveness of tocilizumab in jLS. Objectives: To assess the effectivity of TOC in jlSC patients, who had nonresponse or partial response on conventional therapy. Methods: Participants of the pediatric rheumatology email board were asked, if they follow patients with jlSc, who are treated with TOC. Clinical characteristics and the response to TOC was assessed. Results: Six centers responded to the survey from the email board, with around 800 participatns, and reported 11 patients. The mean age of the patients at disease onset was 5.5 years. Disease duration at time of the intiation of TOC was 53.5. months (range 9 to 109). 5 patients had linear subtype, 3 of them with facial involvement, 2 of them Parry Romberg and one of them coup de sabre. Three had generalized subtype, 2 mixed subtype and 1 limited subtype/morphea. Before starting TOC patients received 10/11 Methotrexate, 7/11 Mycophenolate, 1 abatacept and 1 anti-TNF therapy. Reason to start TOC was in 9 patients increase in Localised Scleroderma Activity Index [1] (mLoSSI). In two patients increased extracutaneous activity was the indication, in one increased activity of arthritis and in the other increased activity of the central nervous system involvement. The mean duration of tocilizumab therapy was 14.75 months. 2 patients received s.c. accoding the poly JIA dosing and all other i.v. There were diferent i.v doses applied, 5 of them 8mg/kg every 4 weeks, one of them 8 mg /kg every three weeks, 1 every two weeks and 1 pateints received 10 mg /kg every 3 weeks. 3/11 received TOC as monotherapy. 8/11 as combination therapy, 6 of them with Methotrexate and one of each with Mycophenolate or Tacrolimus. Therapy success was refelected by a decreased mLoSSI in 8/11 patients and in 6 patients by a decrease in the Localosed Scleroderma Skin Damage Index [1] (LoSDI). No new lesion occured during the treatment and in the patients with Parry Romerg subtype (n=2) no increase in the facial atrophy occured. In 8/8 patients physician global (VAS 0–100) decreased and in 8/8 the patients global disease activity (VAS 0–100) decreased. In 3/3 patients, were it was applicable, the number of acitve joints decreased, in one patients the limb discrepancy decreased. The mean modified Rodnan skin score assessed in 8 patients decreased from the mean value of 9.6 to 5.5. Conclusions: In this small cohort of patients TOC seems to be a promising rescue medication in methotrexate/mycophenolate nonresponsive patients. A prospective controlled study would be important to prove the seen effect in a controlled way. References: Arkachaisri T, Vilaiyuk S, Torok KS, Medsger TA, Jr.: Development and initial validation of the localized scleroderma skin damage index and physician global assessment of disease damage: a proof-of-concept study. Rheumatology (Oxford) 2010, 49(2):373–381. Disclosure of Interest: I. Foeldvari Consultant for: add board chugai, <1000 US, J. Anton Grant/research support from: Grants of Roche, M. Friswell: None declared, B. Bica: None declared, J. de Inocencio: None declared, A. Aquilani: None declared, N. Helmus: None declared